The traveling salesman: computational solutions for TSP applications - Reinelt, Gerhard (Lecture notes in computer science, 1994)
This book is devoted to the famous traveling salesman problem (TSP), which is the task of finding a route of shortest possible length through a given set of cities. The TSP attracts interest from several scientific communities and from numerous application areas. First the theoretical prerequisites are summarized. Then the emphasis shifts to computational solutions for practical TSP applications. Detailed computational experiments are used to show how to find good or acceptable routes for large problem instances in reasonable time. In total, this book meets a tremendous professional need for effective algorithms; it is the most comprehensive and up-to-date survey available on heuristic approaches to TSP solving
Literaturverz. S. [214] - 221
Keywords: Travelling-salesman-Problem